Jemparingan as a source of local wisdom in Mataram: the role of Indonesian traditional arrows in forming the character of nationality - Aziz Abd.; Nining Winarsih (Technium Social Sciences Journal, 2021)
This article aims to examine the role of natural nails VIII in the development of Indonesian archery sport. The method used is the historical research method which includes heuristic, criticism, interpretation and historiography stages. This study describes the philosophical aspects of the typical Mataram archery sport known as jemparingan. the role of Paku Alam VIII in thearrow sport jemparingan, as well as the character value of the jemparingan and its implementation for the younger generation. This paper will provide insight to the public to get to know more about the jemparingan and portrait of the struggle of natural nail VIII in historical studies in Indonesian history.